2019
DOI: 10.18502/ijph.v48i4.1006
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study of Foodborne Disease Using Case Monitoring Data in Shandong Province, China, 2016-2017

Abstract: Background: In order to generate data on the burden of foodborne diseases in Shandong Province, we aimed to use the case monitoring data of foodborne diseases from 2016 to 2017 to estimate. Methods: Data were obtained from the foodborne disease surveillance reporting system with dates of onset from Jan 1, 2016, to Dec 31, 2017, in Shandong, China. Results: The places of food exposure were categorized by settings as follows: private home, catering facility, collective canteens, retail markets, rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As it is known, animal foods can provide hotbeds for pathogens if not stored properly and, thus, cause diseases (Marr, 1999). Similar to other studies (Wu et al, 2019;Finger et al, 2019), multiple foods remain one of the most common vehicles, and this presents difficulties in identifying the specific foods and preventing them from circulation. It should be noted that homemade foods led to more than 30% of cases.…”
Section: Discussionmentioning
confidence: 76%
“…As it is known, animal foods can provide hotbeds for pathogens if not stored properly and, thus, cause diseases (Marr, 1999). Similar to other studies (Wu et al, 2019;Finger et al, 2019), multiple foods remain one of the most common vehicles, and this presents difficulties in identifying the specific foods and preventing them from circulation. It should be noted that homemade foods led to more than 30% of cases.…”
Section: Discussionmentioning
confidence: 76%
“…Analysis of exposed foods of foodborne illnesses in this study, the cases caused by Norovirus, V. parahaemolyticus and Diarrheagenic E. coli, the largest number of food categories involved were aquatic product infection (17.73%, 39.34% and 15.84%, respectively). On the contrary, a study showed the analysis of exposed foods of reported cases in Shandong Province, multiple foods (meaning more than two kinds of food) were the most commonly reported classification [ 30 ]. The reason for the different findings may be that Zhejiang is a coastal province with a vast sea area and various aquatic products.…”
Section: Discussionmentioning
confidence: 99%